2019
DOI: 10.3389/fped.2019.00208
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Indeterminate Interferon-Gamma Release Assay for the Diagnosis of Tuberculosis in Children—A Systematic Review and Meta-Analysis

Abstract: Background: Interferon-gamma release assays (IGRA) are well-established immunodiagnostic tests for tuberculosis (TB) in adults. In children these tests are associated with higher rates of false-negative and indeterminate results. Age is presumed to be one factor influencing cytokine release and therefore test performance. The aim of this study was to systematically review factors associated with indeterminate IGRA results in pediatric patients. Methods: Systematic literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 162 publications
6
38
1
1
Order By: Relevance
“…In addition, the participants' younger age likely affected our observed results. Because of the age-dependent maturation of the immune system, children's IFN-γ production tends to be lower and the contribution of T-cells producing IFN-γ is thought to be less compared to adults [4,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the participants' younger age likely affected our observed results. Because of the age-dependent maturation of the immune system, children's IFN-γ production tends to be lower and the contribution of T-cells producing IFN-γ is thought to be less compared to adults [4,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Screening for Mycobacterium tuberculosis complex (MTBC) infection is done by the widely implemented tuberculin skin test (TST) or the interferon gamma (IFN-γ) release assay (IGRA), both assessing the host's cell mediated immune response to tuberculous antigens [3]. Both tests have their limitations [4]. The TST -employing purified protein derivative (PPD) as antigen-has a low specificity due to cross reactivity with Bacillus Calmette-Guérin (BCG) vaccination and exposure to non-pathogenic environmental mycobacteria [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review and a meta‐analysis that was performed with paediatric TB cases, no statistically significant difference was noted in indeterminate results between different age groups. However, in studies performed in Africa and in non‐human immunodeficiency virus‐infected immunocompromised patients, analyses with T‐SPOT.TB were shown to have a lower frequency of indeterminate results compared to QuantiFERON‐TB analyses . In a study with 2173 subjects, 10 patients were found to have indeterminate QTF‐GIT results.…”
Section: Discussionmentioning
confidence: 95%
“…Screening for Mycobacterium tuberculosis complex (MTBC) infection is done by the widely implemented tuberculin skin test (TST) or the interferon gamma (IFN-γ) release assay (IGRA), both assessing the host's cell mediated immune response to tuberculous antigens [3]. Both tests have their limitations [4]. The TST -employing puri ed protein derivative (PPD) as antigen-has a low speci city due to cross reactivity with Bacillus Calmette-Guérin (BCG) vaccination and exposure to nonpathogenic environmental mycobacteria [5].…”
Section: Introductionmentioning
confidence: 99%